2002
DOI: 10.1002/1521-3935(200207)203:10/11<1466::aid-macp1466>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Materials for cell encapsulation via a new tandem approach combining reverse thermal gelation and covalent crosslinking

Abstract: The contemporary occurrence of a thermal gelation (by the occurrence of a lower critical solubility temperature, LCST) and of a chemical curing has allowed to use biocompatible polyethers (PEG, Pluronic) for mimicking sodium alginate gelation and perspectively substituting it for encapsulation purposes. The final materials were easily formed in cell culture media and perfectly passed a preliminary biocompatibility assessment. Additionally, they showed a stimuli responsive behavior, e.g. in the modulation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
97
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 32 publications
5
97
1
Order By: Relevance
“…The need for more stable hydrogels was identified also by Cellesi et al [67][68][69]. Their approach mimicked the natural thermal gelation of alginate by relying on the occurrence of a physical mechanism, attributed by the thermosensitive nature of Pluronics®, followed by an irreversible chemical mechanism, due to covalent crosslinking by the reaction of groups at the termini of the copolymer.…”
Section: Peo/ppo-based Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for more stable hydrogels was identified also by Cellesi et al [67][68][69]. Their approach mimicked the natural thermal gelation of alginate by relying on the occurrence of a physical mechanism, attributed by the thermosensitive nature of Pluronics®, followed by an irreversible chemical mechanism, due to covalent crosslinking by the reaction of groups at the termini of the copolymer.…”
Section: Peo/ppo-based Systemsmentioning
confidence: 99%
“…It was found that these polymers were biocompatible, and so was their gelation process, which can be performed at physiological temperature and pH, allowing for encapsulation of sensitive drugs and cells [67]. In order to limit steric hindrance phenomena, a similar method was followed with Tetronic® polymers, which are thermosensitive tetra-armed Pluronic® analogues [68].…”
Section: Peo/ppo-based Systemsmentioning
confidence: 99%
“…Given that PEG is highly hydrophilic and generally nonadhesive to proteins or cells, it has found widespread use as a drug carrier [14], and many PEG hydrogels have been produced from aqueous solutions containing linear or branched PEG macromolecules via chemical crosslinking [15][16][17][18]. In addition to hydrogels formed via radical crosslinking reactions, PEG hydrogels have been formed, for example, via Michael-type addition reactions upon mixing with thiol-bearing compounds [19,20] or via the reaction between amino-terminated poly (ethylene glycol) and the herbal iridoid glycoside genipin [21]. In some cases, cell adhesive peptide domains or biodegradable sequences have been introduced into PEG hydrogels to endow them with biological signaling functions [22], including the capacity for growth factor delivery.…”
Section: Introductionmentioning
confidence: 99%
“…In response to this demand, much research has focused on developing new biomaterials or improving existing systems. [1][2][3][4][5][6][7][8][9][10][11][12] While the design criteria driving this research cover as broad a range of material properties as diverse as the array of end-applications, they also share some common goals. Included among these goals is the desire to create biocompatible materials that have tunable material properties which allow optimal tissue regeneration and controllable drug delivery.…”
Section: Introductionmentioning
confidence: 99%